2021
DOI: 10.1111/kykl.12275
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and intimate partner violence

Abstract: The effect of confinement on intimate partner violence is hard to assess, partly because of usual endogeneity problems, but also because the often-used report calls poorly measure that violence. We exploit self-reported survey data from Argentina to study the extent to which the coronavirus pandemic quarantine had unintended consequences on intimate partner violence. The quarantine decree established clear exceptions for heterogeneous subsets of the population and, for reasons plausibly exogenous to the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Internationally, some studies found that, for many women, “COVID-19 coincided with an increase in the frequency or severity of ongoing violence or abuse” [ 20 , 40 ]. Also, as reported by Gibbons et al and Ragavan et al who studied family violence during COVID-19 in Argentina, those at risk of violence became more vulnerable during COVID restrictions, as it was more difficult to find a safe place to make calls and seek help when an abusive partner or, in case of the child abuse, an abusive parent was present [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 98%
“…Internationally, some studies found that, for many women, “COVID-19 coincided with an increase in the frequency or severity of ongoing violence or abuse” [ 20 , 40 ]. Also, as reported by Gibbons et al and Ragavan et al who studied family violence during COVID-19 in Argentina, those at risk of violence became more vulnerable during COVID restrictions, as it was more difficult to find a safe place to make calls and seek help when an abusive partner or, in case of the child abuse, an abusive parent was present [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 98%
“…During the lockdown in Spain, the incidence of IPV among cohabitating couples increased by 24% ( Arenas-Arroyo et al, 2020 ). In a sample of women in lockdown in Argentina, when their partners were also placed in quarantine, women reported a higher prevalence of emotional, sexual, and physical IPV ( Gibbons et al, 2020 ). In Bangladesh, among women experiencing emotional or “moderate” partner physical violence, more than half reported that the violence had increased since the lockdown ( Hamadani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lockdowns imply several risk factors for IPV ( Peterman et al, 2020a ): Cohabitating couples are forced, in a period dominated by anxieties, limitations, and irritation, to spend more time together, thus augmenting the time of exposure to IPV in case of a violent partner. In the study in Argentina, when both partners were placed in quarantine, they spent together, on average, 3.8 h more than couples where only the women had to stay at home ( Gibbons et al, 2020 ). Isolation limits the occasional monitoring of abusive behavior by other people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations